Psychological desensitization levels and their relationship to mental illness among players in the basic and comprehensive Korean university national teams (Al-Muthanna Journal of Sport Education Sciences, 2026)
The research aimed to Identify the psychological level and advanced psychological level, and identify the relationship between advanced psychological level and medical level among players in advanced institutional teams and key senior staff in advanced regions, as well as the descriptive effects of correlational studies. For the northern region of Iraq in volleyball, the researcher used the descriptive method with a correlational study approach due to its suitability to the nature of the research. The original research population consisted of (182) female players from Iraqi university volleyball teams in the northern region, representing (100%). The research community was studied, and the researcher used the Psychological Vitality Scale and the Psychological Flow Scale, both developed by Al-Ta'i (2025). The researcher reached the following conclusions: Female players on the Iraqi university volleyball teams in the northern region exhibited a high level of psychological vitality and a high level of psychological flow. Psychologically, there is a statistically significant correlation between the level of psychological vitality and the level of psychological flow.